UNSUR KEARIFAN LOKAL DALAM LEGENDA “MALIN KUNDANG” - Hasyimsyah Nasution; Salahuddin Harahap; Elpi Sukriah (UIN Sumatera Utara Medan, 2022)
Indonesia is a country that has diversity in terms of ethnicity, nation, race, culture, ethnicity and religion. But nowadays many people forget and even eliminate the culture that has existed since the time of the ancestors which should be used as local wisdom and then developed in accordance with the progress of the times which is in line with the moral teachings of Religion. The legend of Malin Kundang is a local wisdom that contains a lesson, in which there are religious teachings, namely the importance of being devoted to parents.The purpose of this study is to generate and develop local wisdom in the Air Manis sub-district, Padang Selatan district, Padang city so that the community, especially children, still remember the legend of Malin Kundang in order to serve as an advisor to be devoted to parents. The method used in this research is a field study method with a Islamic theology approach. And collect the results of interviews with the Air Manis village community to be used as evidence for research materials. The findings obtained in this study with the local wisdom of the Malin Kundang stone legend located in the Air Manis sub-district, Padang Selatan district, Padang city, made this place one of the most popular and crowded tours to date.